20=x(x+x-6)

Simple and best practice solution for 20=x(x+x-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 20=x(x+x-6) equation:



20=x(x+x-6)
We move all terms to the left:
20-(x(x+x-6))=0
We add all the numbers together, and all the variables
-(x(2x-6))+20=0
We calculate terms in parentheses: -(x(2x-6)), so:
x(2x-6)
We multiply parentheses
2x^2-6x
Back to the equation:
-(2x^2-6x)
We get rid of parentheses
-2x^2+6x+20=0
a = -2; b = 6; c = +20;
Δ = b2-4ac
Δ = 62-4·(-2)·20
Δ = 196
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{196}=14$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(6)-14}{2*-2}=\frac{-20}{-4} =+5 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(6)+14}{2*-2}=\frac{8}{-4} =-2 $

See similar equations:

| -4y+8=2y-10 | | 2(-7y-4)=6 | | 9+4k=4k+9 | | –4(1+t)=–12 | | 16x+2=82 | | 17=–7u–10u | | 15+2.5x=3x+10 | | 2x+100=2 | | 4w-4=-284 | | 1+39x=139x+1 | | 2^t+t-56=0 | | 17x+4=16x+10 | | -4v-9=7 | | 2x−4=24x=x= | | |x+3=12 | | A²-15a+50=0 | | 3(x-4)=-2(-2x+1) | | 34x+26x=180 | | y+63+86=180 | | 5(3+7)−1=3(5+k)+4 | | 5(x+3)=2x+3x=x= | | 2x-68+104=180 | | 6n^2+11n+3=0 | | 21​(4x+8)=4x+8 | | 5n+9​=27​ | | d-12.83=-10.83 | | Y=-35x+105 | | Y=-70x+105 | | (z-9/5)^2=17 | | C=100+12xx=50 | | b-1.8=9.5 | | 1c+3c+2=5c-1 |

Equations solver categories